Financial Heterogeneity and the Investment Channel of Monetary Policy - Ottonello, Pablo; Winberry, Thomas (Econometrica, 2020)
We study the role of financial frictions and firm heterogeneity in determining the investment channel of monetary policy. Empirically, we find that firms with low default risk—those with low debt burdens and high “distance to default”— are the most responsive to monetary shocks. We interpret these findings using a heterogeneous firm New Keynesian model with default risk. In our model, low‐risk firms are more responsive to monetary shocks because they face a flatter marginal cost curve for financing investment. The aggregate effect of monetary policy may therefore depend on the distribution of default risk, which varies over time.